EVALUATION OF ACCIDENT RATE DYNAMICS INVOLVING VULNERABLE ROAD USERS IN THE GOMEL REGION - Кравченя, Ирина; Лебедь, Ирина; Лужанская, Наталья (SWorldJournal, 2021)
The object of the research is the accident rate among vulnerable road users (pedestrians, cyclists, and animal-drawn transport drivers) on the territory of the Gomel region of the Republic of Belarus. In the paper, we carry out the analysis of the estima